Maybe Someday - Book 1 - Hoover, Colleen (New York : Atria Paperback, 2014)
When she discovers that her boyfriend is cheating on her, Sydney, a 22-year-old college student, must decide what to do next, especially when she becomes captivated by her mysterious neighbor Ridge
Keywords: College students -- Fiction; Friendship -- Fiction; Betrayal -- Fiction; Man-woman relationships -- Fiction; Fiction